Rapid Weight Loss and Severe Failure to Thrive Mimicking Lipodystrophy Syndrome in a 1-Year-Old Taiwanese Girl with Costello Syndrome - Yu-Min Syu; Hung-Chang Lee; Jui-Hsing Chang; Chung-Lin Lee; Chih-Kuang Chuang; Huei-Ching Chiu; Ya-Hui Chang; Hsiang-Yu Lin; Shuan-Pei Lin (MDPI AG, 2022)
Costello syndrome (CS) is a type of RASopathy caused mainly by de-novo heterozygous pathogenic variants in the HRAS gene located on chromosome 11p15.5. The phenotype of CS is characterized by prenatal overgrowth, postnatal failure to thrive, curly or sparse fine hair, coarse facial features, and multisystem involvement, including cardiovascular, endocrine, and gastroenterological disorders. We present a one-year-old girl with rapid weight loss and severe failure to thrive. She had gastroesophageal reflux at the age of four months with subsequent rapid weight loss. The loss of fat tissue over the whole body, refractory to a hypercaloric diet, mimicked the presentation of progressive lipodystrophy and masked the dysmorphic features of CS. The final diagnosis of CS was made by whole exome sequencing, which demonstrated a hot-spot, heterozygouspathogenic variant in the HRAS gene (c.34G > A, rs104894229). Our patient illustrates that the excessive energy needs in CS patients may lead to severe failure to thrive and cause challenges in diagnosing CS. This case also highlights the importance of recognizing CS in patients with a history of prenatal overgrowth, polyhydramnios presenting with severe failure to thrive refractory to pharmacotherapy and tube feeding.